PERAN SOSIAL MASYARAKAT PEDULI SAMPAH DALAM MENCIPTAKAN LINGKUNGAN BERSIH DAN SEHAT DI JATIPANDAK, SAMBENG LAMONGAN - Abdul Hadi; Siti Afiyah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2023)
Garbage is something that cannot be avoided in everyday life. The waste problem is a big problem faced by rural settlement communities, the increase in population has implications for the volume of waste produced by the community. To preserve the environment, the community must play an active role in good waste management. The problem in this study is how the role of the Jatipandak village community, Sambeng sub-district, Lamongan regency in good and correct waste management, because the waste management process is still carried out by improper disposal and by burning processes. The purpose of this study was to determine the role of the community in waste management in Jatipandak Lamongan. The method used in this research is the Qualitative Method. which is the study of literature, namely research that is found from data sources obtained through various sources of books, scientific journals related to the problem to be discussed. Based on the results of the research and discussion of research, it can be concluded that community participation in waste management in the village is still not good because there are no facilities and infrastructure as well as a reduced level of public awareness of the importance of good and correct waste management. Suggestions that can be given are to routinely schedule village clean-ups and include a budget for land acquisition that will be used for waste collection temps.